Prevalence and level of antibodies anti-Plasmodium spp. in travellers with clinical history of imported malaria. - Atouguia, Jorge Luís Marques da Silva (2021)
In this study, we show that 40.29% of travellers with a possible history of malaria exposure were positive for anti-Plasmodium spp. antibodies, while these individuals were negative by microscopy. The antibody test described here is useful to elucidate malaria exposure in microscopy-negative travellers from endemic countries.